Study of the pumpkin convective drying. - Pinho, Susana (2013)
The aim of this work is to analyse the effect of convective drying on the nutritional properties of fresh and dried pumpkin (Cucurbita máxima). The samples were analyzed in terms of moisture content, total and reducing sugars, acidity, proteins, lipids, crude fiber and ash. The pumpkin was cut into circular slices dried in a ventilated chamber at different temperatures, ranging between 30 ºC and 70ºC. In addition, the kinetic behaviour was also studied in this temperature band. The results enable us to conclude that the fresh pumpkin has a low content of lipids and a high level of water, sugars, protein and crude fiber. This chemical composition, which is an excellent source of nutritive elements, associated with some components with antioxidant activity, which act as a health-protecting factor, make out of pumpkin an excellent food product, whose consumption should be further encouraged. In addition, it is also possible to conclude that, apparently, the convective drying process has no effect on the nutritional characteristics of the pumpkin, except on sugars and acidity. The influence of the operating condition (the temperature) on the drying kinetics was also analysed. The results show that the increase on the operating temperature strongly accelerates the drying process and a constant rate period is not observed. However, in the range of 30 to 70ºC it was observed that there is a similar kinetic behaviour for all the values of temperature tested. The experimental data for the moisture ratio content with time was fitted, using the software Sigma Plot, v8.0 (SPSS, Inc.), to eight different models, and the two that showed a better performance were the Page and modified Page.